Peningkatan Pendapatan Industri Kecil Tahu di Manokwari Melalui Kemitraan - Aceng Kurniawan (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2023)
The tofu industrial household business in Manokwari Regency is now considered familiar among the people of Manokwari. Because the previous residents had carried out various types of industrial household businesses, both small scale and large scale. Apart from its easy processing, tofu is also a very popular food and can be accessed by all levels of society. As an alternative to getting business capital, it can be done using a partnership system. The aim of this research is to compare the profits obtained by the tofu industry using loan capital from banks and capital from partnerships. The profit obtained by the tofu industry in Manokwari Regency is IDR. 10,942,958,- With a loan system from the Bank, the profit he will get is only Rp. 2,054,070,-.. Of the total profit obtained, because the remainder is used to pay or pay off the principal loan plus interest of Rp. 8,888,888,-. Meanwhile, if you use a profit sharing or partnership system with a profit sharing composition of 70:30, tofu craftsmen will get much bigger profits than using a loan system from a bank, namely IDR. 3,282,887,- and the capital owner or investor gets a profit of Rp. 7,660,070,-, so that the partnership system can increase the income of tofu craftsmen compared to the loan system from banks.